2013
DOI: 10.1371/journal.pone.0059057
|View full text |Cite
|
Sign up to set email alerts
|

XB130, a New Adaptor Protein, Regulates Expression of Tumor Suppressive MicroRNAs in Cancer Cells

Abstract: XB130, a novel adaptor protein, promotes cell growth by controlling expression of many related genes. MicroRNAs (miRNAs), which are frequently mis-expressed in cancer cells, regulate expression of targeted genes. In this present study, we aimed to explore the oncogenic mechanism of XB130 through miRNAs regulation. We analyzed miRNA expression in XB130 short hairpin RNA (shRNA) stably transfected WRO thyroid cancer cells by a miRNA array assay, and 16 miRNAs were up-regulated and 22 miRNAs were down-regulated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 50 publications
1
35
0
Order By: Relevance
“…Based on their study, Takeshita and his colleagues validated the upregulation miR-193a-3p in XB130 knockdown thyroid cancer cells [72]. In addition, overexpression of miR-193a-3p significantly induced both early and late apoptosis in XB130 knockdown thyroid cancer cells [72]. Furthermore, the expression of pri-miR-193a-3P was also increased in XB130 knockdown cells [72].…”
Section: Xb 130mentioning
confidence: 96%
See 2 more Smart Citations
“…Based on their study, Takeshita and his colleagues validated the upregulation miR-193a-3p in XB130 knockdown thyroid cancer cells [72]. In addition, overexpression of miR-193a-3p significantly induced both early and late apoptosis in XB130 knockdown thyroid cancer cells [72]. Furthermore, the expression of pri-miR-193a-3P was also increased in XB130 knockdown cells [72].…”
Section: Xb 130mentioning
confidence: 96%
“…XB130 has been reported as a potent regulator of several miRNAs including miR-193a-3p [72]. Based on their study, Takeshita and his colleagues validated the upregulation miR-193a-3p in XB130 knockdown thyroid cancer cells [72]. In addition, overexpression of miR-193a-3p significantly induced both early and late apoptosis in XB130 knockdown thyroid cancer cells [72].…”
Section: Xb 130mentioning
confidence: 97%
See 1 more Smart Citation
“…Microarray analysis identified that 246 genes were significantly changed in XB130 small hairpin RNA (shRNA)-transfected cells, among which 57 genes were involved in cell proliferation and survival, as well as transcriptional regulation. To further explore the mechanisms that XB130 regulates gene expression associated with cell proliferation or survival, Takeshita et al (50) analyzed miRNA expression in XB130 knockdown WRO cells, based on the estimation that ~30% of all human genes can be regulated by miRNAs (51). They speculated that XB130 may regulate growth-related expression of miRNAs and in this way control the genes associated with cell proliferation or survival.…”
Section: Xb130 In Cancermentioning
confidence: 99%
“…XB130 is aberrantly expressed in human cancers and has been shown to control tumour growth in vivo . XB130 regulates thyroid cancer cell proliferation by controlling microRNA miR-33a, 149a and 193a expression to alter oncogenes Myc, FosL1, and SCL7A5 protein levels (Takeshita et al, 2013).…”
Section: Functionmentioning
confidence: 99%